Clinical legal education during a global pandemic - suggestions from the trenches : the perspective of the Nelson Mandela University - Welgemoed, Marc (PER/PELJ, 2020)
The Covid-19 pandemic has plunged the world into turmoil and uncertainty. The academic world is no exception. In South Africa, due to a nationwide lockdown imposed by government, universities had to suspend all academic activities, but very quickly explored online teaching and learning options in order to ensure continued education to students. As far as Clinical Legal Education, or CLE, is concerned, such online options of teaching and learning could present problems to university law faculties, university law clinics and law students in general, as CLE is a practical methodology, usually following a live-client or simulation model, depending on the particular university and law clinic. This article provides insight into the online methodology followed by the Nelson Mandela University, or NMU. The NMU presents CLE as part of its Legal Practice-module and conventionally follows the live-client model. As the national lockdown in South Africa required inter alia social distancing, the live-client model had been temporarily suspended by the NMU Law Faculty Management Committee and replaced with an online methodology. The aim of this was an attempt to complete the first semester of the academic year in 2020. This online methodology is structured so as to provide practical-oriented training to students relating to a wide variety of topics, including the drafting of legal documents, divorce matters, medico-legal practice, labour legal practice, criminal legal practice, and professional ethics. The online training took place in two staggered teaching and learning pathways in line with the strategy of the NMU, underpinned by the principle of "no student will be left behind." In this way, provision had been made for students with online connectivity and access to electronic devices, students with online connectivity only after return to campus or another venue where connectivity is possible and electronic devices are available, and for students who do not have access to online connectivity and electronic devices at all. The reworked CLE-programme of the NMU, planned for the second semester of the 2020-academic year, will also be discussed in this article. The online methodology followed by the NMU should however not be viewed as definitive or cast in stone in any way. There might be - and there surely are - alternative methodologies, both online and otherwise, that may provide equally good or even better training to CLE students during a global pandemic. Alternative suggestions in this regard will also be discussed in this article. It is hoped that this article will provide inspiration and assistance to university law faculties and law clinics that are struggling to engage with continued practical legal education during the testing and uncertain times brought about by the Covid-19 pandemic. It is further hoped that this article may provide guidance in other difficult and unforeseen future instances that may await CLE. In this regard, it is important to remember that the Fourth Industrial Revolution is rapidly increasing its grip on the world and that CLE will have to adapt to the demands thereof.
Keywords: COVID-19; Clinical Legal Education; Global pandemic; University law clinics; Nelson Mandela University; Online; Legal practice